Interface Modulation of FePc/Porous Ti(HPO4)2 Z‐Scheme Heterojunctions with Ultrafine Ag for Efficiently Photocatalytic CO Oxidation. Issue 6 (27th March 2022) - Zhang, Xinjia; Liu, Yanduo; Chen, Liqiang; Li, Zhijun; Wu, Wei; Bian, Ji; Jing, Liqiang
Abstract : Herein, an integrative Z‐scheme heterojunction of ultrafine Ag‐ (≈ 4 nm) modulated FePc/porous Ti(HPO4 )2 nanosheet (FePc/Ag/TiP NS) with extended spectrum response is designed and fabricated for efficient CO oxidation. The optimal one exhibits approximately tenfold enhancement in photocatalytic activity compared with the bulky TiP counterpart, even outperforming commercial TiO2 (P25). The greatly improved photoactivity is mainly ascribed to the accelerated Z‐scheme charge transfer, and well‐defined isolated central metal ion (Fe 2+ ) in FePc with excellent oxygen activation capacity, along with the extended visible light response. The strengthened charge transfer depends on the interfacial modulation of the ultrafine Ag intentionally embedded in the pores of TiP NS, which enables the electrons of TiP NS migration directionally and induces high‐dispersion FePc controllable assembly on TiP NS with the increased loading amount. Moreover, it is revealed that CO is previously adsorbed on TiP NS via forming –OH–OC intermediate with the surface hydroxyl and subsequently react with the activated O2 by the Fe–N4 sites in FePc to produce CO2 mainly based on in situ diffuse reflectance infrared spectra and near ambient pressure XPS spectra. A new design concept for constructing Ti(HPO4 )2 ‐based Z‐scheme heterojunctions is provided, and the avenues for efficient CO oxidation are paved. Abstract : An integrative Z‐scheme photocatalyst of ultrafine Ag‐modulated FePc/porous Ti(HPO4 )2 nanosheet heterojunction with extended spectrum response is developed for efficient CO oxidation. The controllably introduced Ag drives the electrons of Ti(HPO4 )2 migration directionally toward FePc and induces the high‐dispersion FePc assembly on porous Ti(HPO4 )2 with the increased loading for exposing abundant sites of coordinated Fe–N4 sites to activate O2 .